113k views
5 votes
5x+4(-x-2) = -5x + 2(x-1)+12 solve for x

2 Answers

2 votes

Answer:


\boxed{x = 4.5}

Explanation:


\mathrm{5x + 4( - x - 2) = - 5x + 2(x - 1) + 12}

Distribute 4 through the parentheses

Similarly, Distribute 2 through the parentheses


\mathsf{ 5x - 4x - 8 = - 5x + 2x - 2 + 12}

Collect like terms


\mathsf{ x - 8 = - 3x - 2 + 12}

Calculate the sum


\mathsf{x - 8 = - 3x + 10}

Move variable to L.H.S and change its sign

Similarly, Move constant to R.H.S and change its sign


\mathsf{ x + 3x = 10 + 8}

Collect like terms


\mathsf{4x = 10 + 8}

Calculate the sum


\mathsf{4x = 18}

Divide both sides of the equation by 4


\mathsf{ (4x)/(4) = (18)/(4)}

Calculate


\mathsf{x = 4.5}

Hope I helped!

Best regards!

User Aaronroberson
by
5.7k points
5 votes

Hello!

Answer:


\huge\boxed{x = 4.5}

Starting with:

5x + 4(-x - 2) = -5x + 2(x - 1) + 12

Distribute terms outside of the parenthesis:

5x + 4(-x) + 4(-2) = -5x + 2(x) + 2(-1) + 12

5x - 4x - 8 = -5x + 2x - 2 + 12

Combine like terms:

x - 8 = -3x + 10

Isolate for the "x" variable by adding 3x for both sides:

4x - 8 = 10

Add 8 to both sides:

4x = 18

Divide both sides by 4:

x = 18/4

x = 4.5

Hope this helped! :)

User Hugo Wood
by
6.2k points